Iranian EFL Teachers’ Perception of Teaching Reading Comprehension and Reading Comprehension Strategies across Gender and Experience - Sepideh Mohammadi Bazargani; Zohreh Seifoori; Nasrin Hadidi Tamjid (Iranian Journal of Applied Language Studies, 2022)
The purpose of this research is to investigate Iranian English teachers’ perception of teaching reading comprehension and reading comprehension strategies and their use which can be influenced by individual factors such as gender and teachers’ teaching experience. To serve this purpose, 78 EFL teachers were selected in a stratified manner from West and East Azerbaijan’s language institutes and schools in the second semester of the academic year 2021. This sample included 54 females (=22 experienced, 17 developing, and 15 novices) and 24 males (=1 highly experienced, 6 developing, and 7 novice). To collect the research data, the first three sections of a five-point Likert scale standardized questionnaire was employed to tap teachers’ perception of reading comprehension and the importance of reading strategies. The obtained data were analyzed through Two-Way between Groups Analysis of Variance (ANOVA) to investigate the significant main and interaction effects of teachers’ gender and their teaching experience on their perception of teaching reading comprehension and reading strategies. The results showed that the gender and teaching experience had no significant main or interaction effect on their understanding of the way reading comprehension should be taught or the paramount of reading comprehension strategies. Moreover, the findings unraveled some uncertainties in   teachers’ perceptions of reading comprehension skills and misconceptions regarding the significance of reading comprehension strategies. The findings are pedagogical significant and will be discussed in length.